1986
DOI: 10.1073/pnas.83.11.3776
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence determination of cDNAs for alpha subunits of the guanine nucleotide-binding proteins Gs, Gi, and Go from rat brain.

Abstract: We have cloned cDNAs encoding a subunits of the guanine nucleotide-binding proteins G., G,, and G. and determined their nucleotide sequences. Purified preparations of G, and G. a subunits (Gia and G~a) from rat brain were completely digested with trypsin, and peptides were subjected to amino acid sequence analysis. By screening of a cDNA library from rat C6 glioma cells with a synthetic probe corresponding to a 17 amino acid sequence, a clone encoding the sequence of G~a was obtained. Then, the library was res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 314 publications
(119 citation statements)
references
References 38 publications
3
116
0
Order By: Relevance
“…2, all of the four a-subunits were similarly reacted with anti-c~o antibody (B) which was raised against synthetic oligopeptide (EYGDKERKADSK-MVC) corresponding to the predicted amino acid sequence (94-108) of ozo [3]. The sequence in C~o was the most heterogeneous region among G proteins [3], and the antibody did not crossreact with the other types of o~-subunits, such as c~i, c~s, or c~t (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2, all of the four a-subunits were similarly reacted with anti-c~o antibody (B) which was raised against synthetic oligopeptide (EYGDKERKADSK-MVC) corresponding to the predicted amino acid sequence (94-108) of ozo [3]. The sequence in C~o was the most heterogeneous region among G proteins [3], and the antibody did not crossreact with the other types of o~-subunits, such as c~i, c~s, or c~t (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblot analysis was performed as in [ 11,15,16]. Antibodies used in the present experiments were anti-OLo (A) which was affinity-purified rabbit polyclonal IgG raised against purified O~o and anti-c~o (B) which was also affinity-purified rabbit polyclonal antibody raised against synthetic oligopeptide corresponding to the predicted amino acid sequence (94-108; EYGDKERKADSKMVC) of OLo [3]. This region is specific for C~o and different from the other oL-subunits of G proteins.…”
Section: Purification Of Four Go Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…About 3 x i0s plaques of human genomic library (14) were screened with 32P-labeled rat Gsa as a probe (4 (5) with the sequence of the human Gsa gene suggests that four types of Gsa mRNAs may be generated from a single Gsa gene by alternative splicing as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The a subunits of G protein (Ga) bind guanine nucleotide and are unique to each G protein. Recent progress in molecular cloning of Ga cDNAs revealed that they are highly similar proteins (4). So far, four Gsa (5), three Gia (4,6,41), two Gta (7), and Goa (4) cDNAs were isolated and their sequences were determined (see also ref.…”
mentioning
confidence: 99%